Discovery and Correction of Spurious Low Platelet Counts due to EDTA‐Dependent Pseudothrombocytopenia. Issue 5 (25th November 2014) - Lin, Jianhua; Luo, Yaoling; Yao, Shaoyu; Yan, Miansheng; Li, Jianpei; Ouyang, Wenting; Kuang, Miaohuan
<x xml:space="preserve">Abstract</x> Background Ethylene diamine tetraacetic acid dependent pseudothrombocytopenia (EDTA‐PTCP) is a laboratory artifact that may lead to unnecessary evaluation and treatment of patients. The purpose of this article is to discuss how to identify EDTA‐PTCP and correct spurious low platelet counts in clinical laboratories. Methods We use two criteria to screen for platelet aggregation: (1) an abnormal platelet count in EDTA‐treated blood from a patient lacking clinical signs of a platelet disorder, and (2) an instrument flag for platelet clumps. EDTA‐PTCP was confirmed by microscopic examination for platelet agglutination and by platelet counts that corrected with citrate sample. In addition, the time course of EDTA‐PTCP was investigated in samples from 26 patients anticoagulated with EDTA‐K2 and sodium citrate. Amikacin (5 mg/ml) was added to tubes with EDTA‐K2 or sodium citrate from seven additional cases in order to confirm its dissociative effect on platelet aggregation. Results In our laboratory, the overall incidence of EDTA‐PTCP was approximately 0.09%; and the duration was between 2 weeks and 6 months. EDTA‐PTCP was time‐dependent and occurred as early as 10 min after sample collection. Weaker agglutination could also occur in most corresponding citrate‐treated samples. The dissociative effect of amikacin on platelet agglutination was case‐specific and not concentration‐dependent. Conclusions The method of screening for platelet clumping with the help of XE5000 images is convenient. The decline in the platelet count is related to the length of time and the intensity of chelation. Amikacin supplement is not always effective for correcting platelet counts in vitro.